KOMPOS dan PUPUK CAIR LIMBAH SAWIT UNTUK NUTRISI TANAMAN GAHARU (Aquilaria malaccensis) - Iriyawati, Iriyawati; Widowati, Hening (Universitas Muhammadiyah Metro, 2022)
The purpose of this study was to develop a theoretical aspect regarding the content of liquid and solid waste from a palm oil mill and its effect on the growth of agarwood plants. One of the most promising commodities in the industrial world is cooking oil, so palm oil as a CPO-producing plant is widely developed in Indonesia. Apart from being a producer of CPO, palm oil also has other roles or benefits. From the results of the literature study, it is known that palm oil waste has characteristics, including pH 4.0-6.0, BOD 20,000 mg/l - 60,000 mg/l, COD 40,000 mg/l - 12,000 mg/l, N 500 mg/ l - 900 mg/l, P from 90 mg/l - 140 mg/l, K from 260 mg/l - 400 mg/l, Ca from 1,000 mg/l -2,000 mg/l and Mg from 250 mg/l - 350 mg/l. There are many research journals that examine the content of palm oil waste, all of which state that palm oil waste contains macro elements needed by plants to grow and develop. Therefore, solid and liquid waste from palm oil mills can be used as organic fertilizer. Literature studies or literature studies are carried out from relevant and scientifically accountable sources so that they get valid data and become the basis of a new research. The conclusion of this study is that compost and organic liquid fertilizer from palm oil waste contains the nutrients needed for plant growth, including agarwood plants which are currently in a rare status.